Influence of Theobroma cacao L on the adhesion of Streptococcus mutans - Syaflida, Rahmi; Dohude, Gostry Aldica; Isnandar, Isnandar; Sepriyani, Risa (Journal of Syiah Kuala Dentistry Society, 2023)
Background: Indonesia is a tropical country with various plants ranging from forest products to agriculture and plantations. One of the plants with a lot of beneficial potential as a traditional medicine is the cacao plant (Theobroma cacao L.). Cocoa beans have a high content of polyphenol compounds, which significantly contribute as antioxidants, anti-cancer, anti-diabetes, anti-hypertension, and anti-inflammation. Ketekin, flavonoids, and tannins are compounds in cocoa beans known to have antimicrobial properties. Objective: This study aimed to determine the effectiveness of the antimicrobial power of cocoa bean extract in inhibiting the growth of Streptococcus mutans bacteria. Methods: This research is an experimental laboratory research. The study began with the manufacture of cocoa bean extract made into five concentrations, namely 50%, 25%, 12.5%, 6.25%, and 3.125%. This research was conducted by measuring the diameter of the inhibition zone through the Kirby-Bauer disk diffusion method using chlorhexidine 0.2% positive control and DMSO negative control. Results: The results showed at the largest concentration of 50%, the average value of the inhibitory zone obtained was 19.10 0.25 mm, and the smallest concentration of 3.12% was 7.25 0.29 mm. Conclusion: The study concludes that Cocoa bean extract effectively inhibits the growth of Streptococcus mutans.